Perancangan Media Interaktif Menggunakan Software Articulate Storyline - Mauidhatul Hasanah; Hazrullah Hazrullah; Basrul Basrul (Circuit: Jurnal Ilmiah Pendidikan Teknik Elektro, 2022)
Digital technology has made a great contribution to the education achievement. This technology is especially in the use of various media which need to being developed in learning using interactive multimedia in the teaching matters of a course. This research is inspired by the lack of optimalization used of interactive multimedia in animation programming courses, especially in actionscript programming material. Therefore, the researchers designed an interactive learning media for actionscript programming by using the Articulate Storyline application which called actionscript learning. The problem formulation of this research is how to design and determine the level of feasibility of interactive media for actionscript programming for learning. This study aims to create an actionscript programming interactive learning media that supports learning activities in animation programming courses. However, this study uses the Multimedia Development Life Cycle (MDLC) method. The results obtained from the average value of material experts, media experts, and students are 3.22, 3.1, and  respectively in mean of 3.49, with the percentage of eligibility of 80.5%, 77.4%, and 87.2% in the worthy, worthy and very worthy categories. Thus the interactive learning media of actionscript programming can be said to be feasible to support learning activities in animation programming courses.